PENGGUNAAN MODEL TIME TOKEN ARENDS DALAM MENINGKATKAN KETERAMPILAN BERBICARA PESERTA DIDIK PADA KELAS V DI MADRASAH IBTIDAIYAH 27 LAMASI - Fitria Suciana (Institut Agama Islam Negeri Palopo, 2018)
This research uses classroom action research. The purpose of this study is to improve students' speaking ability in the learning process by using the speaking media card. Implementation of this research is conducted three cycles, each sisklus lasted for two meetings. Subjects in this study were students class V Madrasah Ibtidaiyah 27 Lamasi, which amounted to 28 people. In this research used qualitative and quantitative data analysis techniques. Qualitative data were analyzed by qualitative descriptive analysis. While quantitative data is analyzed by using statistic in the form of mean calculation (mean). The results of this study indicate that the average score of students' speaking skills increases in each cycle. In the first cycle with an average score of 2.03, it increases in cycle II with an average value of 3.18, and increasing again in cycle III, whose average value is 3.75. The conclusion of this research is by using the time token arends model hence speaking skill of class V student Madrasah Ibtidaiyah 27 Lamasi can increase.